2019
DOI: 10.2147/oajc.s184821
|View full text |Cite
|
Sign up to set email alerts
|

<p>Contraceptive Options Following Gestational Diabetes: Current Perspectives</p>

Abstract: Gestational diabetes mellitus (GDM) complicates approximately 7% of pregnancies in the United States. Along with risk factors related to pregnancy, women with a history of GDM also have an increased risk of developing type 2 diabetes mellitus later in life. These women require special consideration when discussing contraception and other reproductive health issues. GDM carries a category 1 rating in the US Medical Eligibility Criteria for all contraceptive methods, which supports safety of the various methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 98 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…According to Shiferaw et al, (2021), women using oral contraceptives had a higher body weight and body fat percentage compared to non-users, but there was no significant difference in BMI between the two groups. Turner et al, (2019). found that oral contraceptive use was associated with a small increase in weight and BMI, but the effect was not clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…According to Shiferaw et al, (2021), women using oral contraceptives had a higher body weight and body fat percentage compared to non-users, but there was no significant difference in BMI between the two groups. Turner et al, (2019). found that oral contraceptive use was associated with a small increase in weight and BMI, but the effect was not clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, as food, exercise, and hormonal state are all associated with glucose tolerance, it is crucial to take these confounding variables into account in any study addressing the possible correlations. 19,20 This study's cross-sectional methodology, which merely permits the detection of relationships rather than demonstrating causation, is one noteworthy flaw. Additionally, the dependence on selfreported dietary fat consumption adds possible recollection bias, and the relatively small sample size may limit the statistical ability to identify significant effects.…”
Section: Discussionmentioning
confidence: 99%